Uso de geotecnologias na seleção de áreas adequadas para aquicultura - Dapieve, Darlan Roque (2023)
Aquaculture is the economic activity involving aquatic organisms. Considering the reduction in the capture of marine fisheries, the global population growth, the increase in the demand for fish protein, especially in recent years, aquaculture has been highlighted as a suitable alternative to these conditions. However, the development of aquaculture has raised many environmental and socioeconomic concerns around the world due to its deregulation and unplanned expansion. In this sense, the use of geotechnologies has provided powerful tools to assist in planning, suitable site selection and aquaculture management, allowing more informed decision-making. These technologies allow versatile, fast, and accurate analysis, with large spatial data sets and combined use with various mathematical and statistical techniques, which enable the creation and spatial analysis of multiple scenarios. This process is generally based on the classification of the suitability sites based on suitability factors and constraints to the development of aquaculture activity. This work was divided into three chapters. The first one consists in a systematic review of scientific articles from the Scopus and Web of Science databases that used geotechnologies to select suitable sites for aquaculture. These articles were characterized by publication year, country of authors affiliation and journals of publication. By the synthesis methodology, studies that used suitability factors and constraints for aquaculture site selection in ground-excavated ponds were selected, analyzed and discussed on the main factors mentioned. The second chapter involves the use of geotechnologies tools and multicriteria analysis to suitable site selection for Nile tilapia production in ground excavated ponds in the 54 cities that comprise the Western region of the state of Paraná. Thematic maps were produced containing the suitability classification according to a series of criterions and factors established, and a map of the general suitability of the area under study, which proved to be mostly suitable for the activity and with large potential of expansion. Finally, in the third chapter, mapping and characterization of ground-excavated ponds in the city of Assis Chateaubriand was conducted, and estimated production potential of Nile tilapia for the years 2018, 2020 and 2022, using geotechnologies tools. A clear development of fish farming activity in the municipality was observed in recent years, with an increase in the number and size of the ponds and also in the fish farming properties.